Comprehensive evaluation of frost mulberry leaves of 21 mulberry varieties - Tian, Jie; Liu, Bingxiang; Fan, Zhitong; Yang, Jingyan; Wu, Yibo; Tian, Xinyuan; Jia, Chenyang; Wen, Haichao; Zhang, Bingying; Li, Hongjiao (Frontiers in Plant Science, 2025)
IntroductionMulberry, a medicinal and edible plant, exhibits significant pharmacological effects, including immune enhancement, blood lipid and glucose reduction, and tumor inhibition, due to the abundance of nutrients and bioactive components in its leaves. However, traditional mulberry breeding has primarily focused on developing high-yielding, high-quality, stress-resistant, and mechanizable leaf-type mulberry varieties, leading to a relatively uniform product output. With the increasing diversification of mulberry applications, the criteria for variety selection and quality evaluation have become more stringent.MethodsIn this study, 21 mulberry varieties were selected as experimental materials to evaluate the variations in nutritional quality, functional components, and antioxidant properties of frost mulberry leaves across different varieties. Principal component analysis (PCA) was employed to determine key evaluation indicators. Subsequently, the entropy‐weight method was employed to assign weights to these core indicators, and grey relational analysis (GRA) was applied, to comprehensively assess the overall quality of frost mulberry leaves from the 21 varieties.ResultsThe results indicate that, in terms of nutritional quality, 'Da 10' exhibited the highest free amino acid content; however, its low soluble sugar content negatively affected leaf texture. In contrast, 'Jiang Mi Guo Sang', 'Lv Shen Zi 2', and 'Ju Shen' demonstrated superior overall performance. Regarding functional components, 'Tang 10', 'Da Yi Bai', 'Da Bai E', and 'Lv Shen Zi 1' excelled across all indicators. Concerning antioxidant capacity, 'Da Bai E', 'Jiang Mi Guo Sang', 'He Lan Sang', and 'Ju Shen' ranked highly, while 'Da 10', 'Da Yi Bai', 'Hong Guo 1', and 'Da Bai E' exhibited higher enzyme activity. PCA identified 10 core indicators related to nutritional quality, functional components, and antioxidant capacity, with a cumulative variance contribution rate of 83.752%. The entropy weight method was then used to assign weights to these indicators, and the final grey relational degree, calculated using grey system theory, ranged from 0.476 to 0.785.ConclusionThis study demonstrates that the varieties 'Da Bai E', 'Da Yi Bai', 'Da 10', 'He Lan Sang', and 'Tang 10' exhibit superior overall quality and high nutritional value, providing theoretical support for the subsequent selection, cultivation, and utilization of mulberry varieties.